Stable and continuous long-term enzymatic reaction using an enzyme-nanofiber composite - Lee, Jin Hyung; Hwang, Ee Taek; Kim, Byoung Chan; Lee, Sun-Mi; Sang, Byoung-In; Choi, Yong Su; Kim, Jungbae; Gu, Man Bock (Springer Verlag, 2007)
This study shows the preparation and application of enzyme-nanofiber composites for long-term stable operation. The enzyme-nanofiber composite was prepared by coating an enzyme aggregate, the esterase from Rhizopus oryzae, on the surface of the nanofibers. After immobilization on the nanofiber, the apparent K (m) for the immobilized esterase was 1.48-fold higher than that of the free esterase, with values of 0.98 and 1.35 mM for the free and immobilized enzymes, respectively. It was found that enzyme-nanofiber was very stable, even when the fibers were shaken in glass vials, preserving 80% of the initial activity for 100 days. In addition, the enzyme-nanofiber composite was used repeatedly in 30 cycles of substrate hydrolysis and still remained active. Consequently, the esterase-nanofiber composite was employed within a continuous reactor system to evaluate its use in a long-term and stable continuous substrate hydrolysis reaction. It was found that the production of p-nitrophenol was stable for at least 400 h. This study demonstrates that the enzyme-nanofiber composite can be used in both repeated-batch mode and a continuous mode for a long-term stable operation.